Near-Infrared Light-Triggered Thermo-responsive Poly(N-Isopropylacrylamide)-Pyrrole Nanocomposites for Chemo-photothermal Cancer Therapy - Ha Hee Shin (Nanoscale Research Letters, 2020)
Abstract The combination therapy based on multifunctional nanocomposites has been considered as a promising approach to improve cancer therapeutic efficacy. Herein, we report targeted multi-functional poly(N-isopropylacrylamide) (PNIPAM)-based nanocomposites for synergistic chemo-photothermal therapy toward breast cancer cells. To increase the transition temperature, acrylic acid (AAc) was added in synthetic process of PNIPAM, showing that the intrinsic lower critical solution temperature was changed to 42 °C . To generate the photothermal effect under near-infrared (NIR) laser irradiation (808 nm), polypyrrole (ppy) nanoparticles were uniformly decorated in PNIPAM-AAc. Folic acid (FA), as a cancer targeting ligand, was successfully conjugated on the surplus carboxyl groups in PNIPAM network. The drug release of PNIPAM-ppy-FA nanocomposites was efficiently triggered in response to the temperature change by NIR laser irradiation. We also confirmed that PNIPAM-ppy-FA was internalized to MDA-MB-231 breast cancer cells by folate-receptor-mediated endocytosis and significantly enhanced cancer therapeutic efficacy with combination treatment of chemo-photothermal effects. Therefore, our work encourages further exploration of multi-functional nanocarrier agents for synergistic therapeutic approaches to different types of cancer cells.